Efecto del hidrogel y vermicompost sobre la productividad del pasto cuba OM-22 (Pennisetum purpureum x P. Glaucum) en época seca - Bravo Macay, Lorena Mercedes (2021)
The main objective of the research was to evaluate the effect of the hydrogel and vermicompost on the productivity of Cuba OM-22 grass (Pennisetum purpureum x P. Glaucum) in the dry season. The experiment was developed during the dry season of 2019, in the grass research area at ESPAM MFL. The treatments consisted of four levels of hydrogel (0, 50, 100, 150 kg ha-1 ) and four levels of compost (0, 20, 30 and 40 t ha-1 ). The design used was randomized complete blocks (DRCB) with 16 treatments, three repetitions and 48 experimental units. The main variables recorded were fresh and dry biomass yield (t ha-1 ) at 45, 60, 75 and 90 days after the equalization cut. The effect of the hydrogel was only significant (p≤0.05) at 45 and 60 days after cutting, where the dose of 50 kg ha-1 showed the highest production. Vermicompost did not show significant effects (p>0.05) on the production of fresh and dry biomass at any of the cutting frequencies evaluated. At the frequencies of 75 and 90 days, neither the hydrogel nor the compost show effects on production, regardless of the doses evaluated.